PENGEMBANGAN BUKU PANDUAN APLIKASI ADOBE PHOTOSHOP CS6 DALAM MENINGKATKAN KETERAMPILAN EDITING FOTO SISWA TUNARUNGU TINGKAT SMALB - NUR HUMAIDI, HADZIQ; MASITOH, SITI (Jurnal Pendidikan Khusus, 2018)
Adobe Photoshop photo editing skills need to be taught to the students? with deaf because it suits their skill and potential. The purpose of this study is to develop an Adobe Photoshop CS6 guidance book which suit the students with deaf and to test its suitability. Books? practicality and validity test is based on the assessment of material expert, subject teacher, and limited testing toward 3 students with deaf in the XI grade of SLBN Pandaan which the shows good as the result. Based on the practicality and validity test, Adobe Photoshop photo editing skills guidance book is valid and suitable to be used in teaching. The effectiveness test used gain score analysis pretest and posttest toward 6 students with deaf in the%2 grade of SLBN Pandaan, the score shows 0,72 which is a high score. In conclusion, Adobe Photoshop photo editing skills guidance book is effective to be used in developing students with deaf at SMALB photo editing skill.